Tunable Magnetocaloric Effect in Ni-Mn-Ga Microwires. Issue 1 (December 2018) - Qian, Mingfang; Zhang, Xuexi; Wei, Longsha; Martin, Peter; Sun, Jianfei; Geng, Lin; Scott, Thomas; Peng, Hua-Xin
Abstract Magnetic refrigeration is of great interest due to its high energy efficiency, environmental friendliness and low cost. However, undesired hysteresis losses, concentrated working temperature interval (WTI ) and poor mechanical stability are vital drawbacks that hinder its practical application. Off-stoichiometric Ni-Mn-Ga Heusler alloys are capable of giant magnetocaloric effect (MCE) and tunable transformation temperatures. Here, by creating Ni-Mn-Ga microwires with diameter of 35–80 μm using a melt-extraction technique, negligible hysteresis and relatively good mechanical stability are found due to the high specific surface area (SSA) that reduces incompatibility between neighboring grains. The high SSA also favors the element evaporation at high temperatures so that the transformation temperatures can be feasibly adjusted. Tunable magnetocaloric effect owing to different magneto-structural coupling states is realized by (i) composition design and subsequent tuning, which adjusts the temperature difference between the martensite transformation (MT) and the magnetic transition, and (ii) creation of gradient composition distribution state, which manipulates the MT range. Magnetic entropy changeΔS m −18.5 J kg−1 K−1 with relatively concentratedWTI andWTI up to 60 K with net refrigeration capacity 240 J kg−1 at 50 kOe are demonstrated in the present Ni-Mn-Ga microwires. This criterion is also applicable for other small-sized materials.